Aujeszky’s Disease (Pseudorabies). An old threat in current pig industry? Part I. Pathogenetic information and implications - PAPAGEORGIOU (Κ.Β. ΠΑΠΑΓΕΩΡΓΙΟΥ) K. V.; BURRIEL, A. R.; FILIOUSSIS (Γ. ΦΙΛΙΟΥΣΗΣ) G.; PSYCHAS (Β. ΨΥΧΑΣ) V.; NAUWYNCK, H.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. (Journal of the Hellenic Veterinary Medical Society, 2017)
Aujeszky’s disease (AD) (or Pseudorabies) is an important viral disease of swine causing neurological signs in neonatal pigs, respiratory problems in fatteners and reproductive disorders in breeding stock. Glycoproteins and enzymes of the AD virus (ADV) and their interactions with the cellular components majorly determine its pathogenesis. After primary replication in the epithelia of the upper respiratory tract, ADV travels via the nerves to the central nervous system and via the blood to secondary replication sites (lymph nodes, lungs, uterus etc). Depending on the age of the affected swine, it can cause neonatal mortality due to neurological disease, respiratory disease in growing and adult pigs and reproductive disorders in breeding animals. One of the characteristic features of ADV is latency. In this paper, its major points on etiology, pathogenesis, clinical and post mortem findings and diagnosis are presented.